A histological and immunohistochemical study of tissue reactions to solid poly(ortho ester) in rabbits - Ekholm, M.; Helander, P.; Hietanen, J.; Lindqvist, C.; Salo, A.; Kellomäki, M.; Suuronen, R. (International journal of oral and maxillofacial surgery, 2006)
In many cases only the temporary presence of a biomaterial is needed in tissue support, augmentation or replacement. In such cases biodegradable materials are better alternatives than biostable ones. At present, biodegradable polymers are widely used in the field of maxillofacial surgery as sutures, fracture fixation devices and as absorbable membranes. The most often used polymers are aliphatic polyesters, such as polyglycolic acid (PGA) and polylactic acid (PLA). Poly(ortho ester) is a surface eroding polymer, which has been under development since 1970, but is used mostly in drug delivery systems in semisolid form. The aim of this study was to evaluate the tissue reactions of solid poly(ortho ester) (POE), histologically and immunohistochemically. Resorption times and the effect of 2 different sterilization methods (gamma radiation and ethylene oxide) upon resorption were also evaluated. Material was implanted into the tibia and subcutaneously into the mandibular ramus area of 24 rabbits. Follow-up times were 1–10, 14 and 24 weeks. Histological studies showed that POE induces a moderate inflammation in soft tissue and in bone. At 24 week follow-up, inflammation was mild in soft tissue and moderate in bone. In immunohistochemical studies, no highly fluorescent layer of tenascin or fibronectin was found adjacent to the implant. Resorption of gamma-sterilized rods was faster than ethylene oxide-sterilized rods. The total resorption time was more than 24 weeks in both groups. Clinically the healing was uneventful and the implants the well tolerated by the living tissue. This encourages these authors to continue studies with this interesting new material to search for the ideal material for bone filling and fracture fixation.